Somatic mutations in the DNA repairome in prostate cancers in African Americans and Caucasians - Yadav, Santosh (Oncogene, 2020)
Most hereditary tumors show aberrations in DNA repair genes or their regulators. In contrast, only a minority of sporadic tumors show alterations in these genes. As a result, genomic instability is currently considered an enhancer of tumorigenesis rather than an obligatory event in this process. However, tumor heterogeneity presents a significant technical challenge for most cancer genomics studies performed at less than 100× mean resolution depth. To address the importance of genomic instability in prostate carcinogenesis and tumor progression, we performed ultrahigh depth exome sequencing of 124 DNA damage repair/response (repairome) genes in 63 tumors and matched normal tissue samples in African Americans and Caucasians. The average sequence depth was 712-fold for DNA isolated from normal tissue and 368-fold for FFPE tumors. We identified 671 somatic mutations in tumors from African Americans and 762 somatic mutations in tumors in Caucasians. The most frequently mutated DNA repairome genes were EXO1, ATR, POLQ, NEIL3, ERCC6, BRCA2, BRCA1, XPC, JAG1, RPA1, POLE, ATM, and LIG1 in African American men, and POLQ, NEIL3, POLB, BRCA2, EXO1, ERCC6, ATR, RBBP8, BRCA1, ATM, JAG1, XPC, and POLE in Caucasians. We found that 89% of tumors had at least one mutation in nucleotide excision repair pathway genes in African Americans, whereas >40% of tumors had mutations in base excision repair pathway genes in Caucasians. We further identified a marginal increase in mutation rate in tumors in African Americans with increasing age. Tumors in Caucasians did not show a correlation with age, but a progressive increase in the mutation rate was observed at higher Gleason scores. Our data reveal significant differences in the molecular signatures in the DNA repairome in prostate cancer between African Americans and Caucasians. These data also have substantial implications regarding the well-known health disparities in prostate cancer, such as the higher mortality in African Americans than Caucasians.